Klasifikasi Kualitas Produk Mesin Pertanian Berdasarkan Evaluasi Kinerja Algoritma Random Forest - Hakim, Irma; Asdi, Asdi; Lubis, Mhd. Dicky Syahputra; Harahap, Mely Novasari; Bara, Lokot Ridwan Batu (LPPM STIKOM Tunas Bangsa, 2025)
This study aims to classify product quality in the agricultural industry using the Random Forest algorithm. The data used includes various inspection result parameters, such as dimensions, weight, product color, quality status, defect image, inspection time, temperature, machine speed, and indicator lights. The model is developed to classify products into